The Role of Brand, Product Quality, and Price on Consumer Purchase Interest in The Local Shoe Brand Aerostreet - Fikri Haimal Putra; Husni Amala; Rezkiah Nala Putri (Yayasan Adra Karima Hubbi, 2024)
This study employs a quantitative method to measure variables related to consumer purchase interest in Aerostreet shoes. The population involves active students and the general public who have purchased the product. Samples were selected through random sampling classification from students in semesters 1-5 and the general public. Data analysis uses multiple linear regression to examine the influence of promotion, brand, and product quality on consumer purchase interest. PLS-SEM is used as an analysis tool with SMARTPLS 3.3.0, producing valid and reliable instruments. The multiple linear regression analysis results show that product quality and price significantly influence purchase interest, while the brand is not significant. Discriminant validity tests and VIF indicate model fit. Model fitness tests show that the Estimated Model is in line with the data, with an R Square of about 66.4%. Blinding tests show the model can predict about 53.8% of the variation in purchase interest. Hypothesis tests confirm the significant influence of product quality and price, while the brand is not significant. This study contributes to understanding the factors influencing consumer purchase interest in Aerostreet shoes and provides marketing strategy recommendations.